PENDEKATAN PERENCANAAN STRATEGIS UNTUK ADMINISTRASI PERPAJAKAN DI RUMAH SAKIT (STUDI KASUS RSU BHAKTI YUDHA DEPOK JAWA BARAT) - Abdul Rahman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
Hospital represent one of effort institution which active in service of health. Hospital represent Income Tax (PPh) subject and of Value Added Tax (PPN) subject if delivering Goods which is PPN Object than Rp.600.000.000,-. RSU Bhakti Yudha Depok represent hospital which located in town region of Depok representingregion of Dati II. As Subjek of Tax, RSU Bhakti Yudha Depok do obligation of its taxation, among others PPh, PPN and PPh Section 21 to all its employees.From strategic planning approach, use SWOT analysis, get result that strengths, Weaknesses, Opportunities and Threats from this hospital. With combine these factors can be formulated Vision, Missions and Goals obligation of taxation of RSU Bhakti Yudha and some strategies to reach them.